Driver gene alterations in NSCLC patients in southern China and their correlation with clinicopathologic characteristics - Deng, Lingna; Li, Jinbang; Qiu, Zhanlong; Wang, Yanfen (Frontiers in Genetics, 2024)
Introduction In this study, we aimed to explore the relationship between clinicopathological features and driver gene changes in Chinese NSCLC patients. Methods Amplification refractory mutation system PCR was used to detect the aberrations of 10 driver oncogenes in 851 Chinese NSCLC patients, and their correlation with clinicopathological characteristics was also analyzed. Moreover, three models of logistic regression were used to analyze the association between histopathology and EGFR or KRAS mutations. Results The top two most frequently aberrant target oncogenes were EGFR (48.06%) and KRAS (9.51%). These were followed by ALK (5.41%), HER2 (2.35%), MET (2.23%), RET (2.11%), ROS1 (1.88%), BRAF (0.47%), NRAS (0.24%), and PIK3CA (0.12%). Additionally, 11 (1.29%) patients had synchronous gene alterations in two genes. The main EGFR mutations were exon 21 L858R and exon 19-Del, which accounted for 45.97% and 42.79% of all EGFR mutations, respectively. Logistic regression analysis showed that the frequency of EGFR mutations was positively correlated with women, non-smokers, lung adenocarcinoma, and invasive non-mucinous adenocarcinoma (IA), and negatively correlated with solid nodule, micro-invasive adenocarcinoma, and solid-predominant adenocarcinoma. KRAS mutations were positively associated with men and longer tumor long diameters and negatively correlated with lung adenocarcinoma (P < 0.05 for all). Conclusion Our findings suggest that the EGFR mutation frequency was higher in women, non-smokers, lung adenocarcinoma, and the IA subtype in lung adenocarcinoma patients, while the KRAS mutation rate was higher in men and patients with longer tumor long diameter and lower in lung adenocarcinoma patients.